Domain-specific influence on Facebook: How topic matters when assessing influential accounts in four countries - Camila Mont'Alverne; Amy Ross Arguedas; Sumitra Badrinathan; Benjamin Toff; Richard Fletcher; Rasmus Kleis Nielsen (Journal of Quantitative Description: Digital Media)
Against the backdrop of rising concern over misinformation and disinformation, a growing number of studies have considered the important role played by influential social media accounts when particular news stories attract attention online—with special attention given to Facebook, the most widely-used social network for news. However, little is known about what kinds of accounts are among the most influential information curators on Facebook, and where news organizations fit into this broader landscape. In this study, we examine how influence on Facebook plays out across different national contexts and different topics. We draw on a unique dataset from CrowdTangle, sampling over a six-month period in 2021 across four countries (Brazil, India, the United Kingdom, and the United States). We compare what kinds of sources (e.g., news organizations, politicians, or other kinds of influential accounts and groups) are among the most influential accounts in each location when it comes to three specific subjects: COVID-19, political leaders in each country, and climate change—which we also compare to general queries that do not specify a subject domain. Our findings show that the types of influential accounts on Facebook vary considerably by subject domain and country. News media accounts are among the largest share of these influential accounts in each country, but not necessarily the types of news media organizations presumed to be most influential offline.